2021
DOI: 10.2147/ijwh.s286088
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fear and Knowledge of COVID-19 on Preventive Practice Among Pregnant Women Who Attend Antenatal Care in Northwest Ethiopia, 2020: Institution-Based Cross-Sectional Study

Abstract: Background:The novel coronavirus disease 2019 (COVID-19) pandemic has infected over one million individuals with almost 50,000 deaths worldwide. COVID-19 is currently a global health threat and a public health emergency. Therefore, accurate and up-to-date information regarding prevention and control methods is essential. Objective: The aim of the study was to assess the effects of fear and knowledge of COVID-19 on preventive practices among pregnant women who attend antenatal care in northwest Ethiopia, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
3
8
0
2
Order By: Relevance
“…Our study also revealed that like attitude, fear has also a positive impact on preventive practice, indicating the more fear, the more preventive practice. A similar outcome was reported by (27,31). Ostensibly, this outcome could seem controversial but it represents the significant influence of fear on changing someone’s behavior or attitude towards preventive practice.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also revealed that like attitude, fear has also a positive impact on preventive practice, indicating the more fear, the more preventive practice. A similar outcome was reported by (27,31). Ostensibly, this outcome could seem controversial but it represents the significant influence of fear on changing someone’s behavior or attitude towards preventive practice.…”
Section: Discussionsupporting
confidence: 91%
“…La réduction des interventions essentielles en matière de santé maternelle durant la période de la pandémie a été observée dans beaucoup de pays [ 8 , 9 ]. Si la femme enceinte est permanemment en questionnement sur l´issue de la grossesse et le bien-être de son enfant, la pandémie a infligé un stress de plus avec un état d´anxiété et de dépression à celui préexistant [ 10 ].…”
Section: Discussionunclassified
“…Knowledgeable to COVID-19 : Participants who scored above the mean (12.47) on 11 knowledge assessment questions. 36 …”
Section: Methodsmentioning
confidence: 99%